GONDANG SITOLUPULU TOLU DALAM UPACARA PESTA TUGU RAJA SILAHISABUNGAN - Anggiat Purba (Saraswati)
Gondang SitolupuluTolu is a type of traditional music ensemble comprised of three instruments namely; Sarunei, taganing, Gordang and Ogung instruments. The existence Gondang SitolupuluTolu today, still considered important in the social culture of the region Silahisabungan Medan North Sumatra province, because music is considered as a medium of expression that can describe the disclosure of customs value and as a manifestation of religious communities Silahisabungan. Gondang SitolupuluTolu traditional music is one that can survive in their communities, because music is still used as the primary means sacred or media that can not be separated King Memorial Ceremony celebration party Silahisabungan which hitherto still exist conducted in each year based on custom and tradition that still applies in the community or clan groups Silahisabungan in Medan North Sumatra province. Keywords: Gondang Sitolupupu Tolu, Pesta Tugu, Function